Safe at home. (American City & County, 2007)
This section offers news briefs from U.S. state governments as of August 1, 2007. Atlanta-based National Conference of Black Mayors (NCBM) has contracted with NTI Group to provide real-time, mass notification services for NCBM members. The Kansas Department of Corrections has purchased a wireless monitoring system from Omnilink Systems to track convicted offenders. Henrico County, Virginia has contracted with Sigma Communications to implement an emergency notification system for sending emergency bulletins to residents via telephone, e-mails and pagers.